The relationship between personality traits and English language speaking anxiety among Faculty of Economics and Management undergraduates in UKM - Huda Bahrudin,; Zaini Amir, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
The role of personality in second and foreign language learning are acknowledged and are viewed as useful predictors of language learning success. Personality can either encourage or inhibit language learning, and language anxiety among students often stem predominantly from speaking situations. The present study investigated the personality traits and English language speaking anxiety among Faculty of Economics and Management (FEP) undergraduates in UKM. Additionally, the study examined any significant relationship between the personality traits and English language speaking anxiety among FEP UKM students. A total of 104 FEP undergraduate students from Business, Economics, Accounting, and Entrepreneurship majors across different years of study were selected using purposive random sampling to participate as respondents to this quantitative study. The Big Five Inventory (BFI) and English Language Speaking Anxiety Scale (ELSAS) were used to identify personality traits and levels of English language speaking anxiety respectively. Results were tabulated and run through SPSS to obtain a correlation matrix. The results show Openness, Agreeableness, and Conscientiousness as the most recurring personality trait of FEP undergraduates. A majority of FEP undergraduates have moderate level of Communication Apprehension and Fear of Negative Evaluation. Pearson Correlatives show a positive relationship between Communication Apprehension and Fear of Negative Evaluation with Neuroticism, but a negative relationship with Extraversion.